Comparison of F1 and F2 generations of commercial hybrid maize - dos Santos, Osmar Souza; Manara, Wilson; Manara, Nublea Teresa Felkl; Raupp, Ricardo Oscar; Ribeiro, Nerinéia Dalfollo; Tsukano, Maria Michiko Kusano (Pesquisa Agropecuaria Brasileira, 1993)
Two experiments were carried out at the Federal University of Santa Maria, RS, Brazil, aiming to compare F1 and F2 grain yields of commercial maize (Zea mays L.) hybrids Agroceres 28, Agroceres 64-A, Cargill 408, Cargill 501, Cargill 511 and Pioneer 3212; two NPK fertilizer levels were used. During 1987/88 growing.season part of F1 was grown in order to obtain the F2 generation and in 1988/89 the two generations were compared. The experimental design was a 2x6 factorial split plot design in which the fertilizer levels formed the main plots and o F1 and F2 generations of the hybrids were the sub-plots. F1 had higher values than F2 for final population, plant height, height of first cob and numbers of cobs per plant regardless of fertilizer levels. F2 generation had a 12,5% lower grain yield than F1. There were no differences in grain characteristics among generations.